Factors Related To The Incidence of Abortion at Tora Belo Hospital - Deslianti Daniel Samel (Jurnal Indonesia Sosial Sains, 2023)
Abortion is an event that still occurs in many communities both intentionally and because of unwanted things. The increase continues to occur every year based on many of the socio-religious, psychological, educational status, economic status and physical condition of a mother. At Tora Belo Hospital, every year there is a decrease in the incidence of abortion in the register data obtained in 2021 as many as 113 patients and in 2022 as many as 117 patients there is a slight increase in the incidence of abortion. This study aims to determine the factors associated with the incidence of abortion at Tora Belo Hospital. This study used a cross sectional study with secondary hospital data. The results of simultaneous f and partial t tests found that age, educational status and economic status were related to the incidence of abortion, while body mass index and abortion history were not significantly related to the incidence of abortion at Tora Belo Hospital